Evaluating the Nonlinear Population-Economic Growth Nexus in MENA Countries - BENGANA, Ismail Mohamed; ADELEYE, Bosede Ngozi; BOUKHELKHAL, Abdelaziz Abdelkhader; OKAFOR, Victoria ISIOMA; Alnefai, Abdulah HAMOUD; Salim , Eltahir Ibrahim Elnour (Journal of Ecohumanism, 2024)
The relation between population growth and economic growth is a complex one, and the historical quantitative evidence is ambiguous. This study contributes to the population-economic growth literature by interrogating whether the relationship is monotonic or if a turning point exists. Using panel data on a sample of 19 MENA countries from 1965 to 2018 and deploying the PSCE and FGLS techniques, the results reveal inter alia: (1) a U-shaped relation exists; (2) unemployment and financial development are negative predictors of economic growth; and (3) trade and inflation rate are positive predictors. Policy recommendations are discussed.